Performansi Residential Air Conditioning Hibrida Dengan Standby Mode Menggunakan Refrigeran HCR-22 Untuk Pendingin Dan Pemanas Ruangan - Eko Prasetyo; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The hybrid of Residential Air Conditioning (RAC) is a cooling system that utilizes cooling effect and warming effect of refrigeration simultaneously to improve machine performance. Chiller is one of cooling system that used to cool liquid (brine or water) by using HCR-22 refrigerant as the cooling medium and the brine serves as a secondary refrigerant to cooling the room indirectly. Standby mode is a cooling method without using ice or cooling methods from the chiller directly. In this study, the RAC with standby mode is done without cooling load so resulting in a performance with Coefficient of Performance average is 2.46, Factor of Performance average is 3.42, and Total of Performance average 5.88. Then, the average temperature of cooler room is 22.54 ˚C. The average temperature of warmer room is 38.87 ˚C was able to contribute both as warming and it can stability of refrigeration system during process.Keywords : Hybrids RAC, Chiller, Standby mode, Performance, Temperature